Designing an Integrated Digital Marketing Governance Model for Products Made by Inmates in Correctional Institutions - Melanie Mardolna Sine; Eko Sediyono; Evi Maria (SISTEMASI, 2026)
This study aims to develop an integrated digital marketing governance model for products made by inmates in correctional institutions. The research addresses the lack of integration in the marketing activities of inmate-produced products, where product management, digital promotion, sales transactions, and activity reporting are largely performed through fragmented and manual processes. The study adopts the Design Science Research (DSR) methodology, encompassing the stages of system requirements identification, model design, system architecture development, business process visualization, and conceptual evaluation through expert review and focused group discussions. The proposed model integrates product management, digital promotion, sales transactions, activity documentation, digital monitoring, and institutional oversight into a unified digital marketing governance framework. The conceptual evaluation involved four experts, comprising two correctional rehabilitation officers and two vocational program managers, who confirmed that the proposed model adequately addresses the digital marketing management needs of correctional institutions. The findings further demonstrate that the use of social media, online marketplaces, and digital communication platforms can effectively support the marketing of inmate-produced products while maintaining appropriate institutional oversight and security controls. This study contributes by proposing an institutionally governed digital marketing model that can be implemented through a low-cost digital architecture, making it particularly suitable for organizations operating in environments with strict digital access restrictions.